Decolonizing Health Governance: A Uganda Case Study on the Influence of Political History on Community Participation - Moses Mulumba; Ana Lorena Ruano; Katrina Perehudoff; Gorik Ooms (Harvard FXB Center for Health and Human Rights, 2020)
This paper presents a case study of how colonial legacies in Uganda have affected the shape and breadth of community participation in health system governance. Using Habermas's theory of deliberative democracy and the right to health, we examine the key components required for decolonizing health governance in postcolonial countries. We argue that colonization distorts community participation, which is critical for building a strong state and a responsive health system. Participation processes grounded in the principles of democracy and the right to health increase public trust in health governance. The introduction and maintenance of British laws in Uganda, and their influence over local health governance, denies citizens the opportunity to participate in key decisions that affect them, which impacts public trust in the government. Postcolonial societies must tackle how imported legal frameworks exclude and limit community participation. Without meaningful participation, health policy implementation and accountability will remain elusive.